INOVASI KURIKULUM DALAM PENGEMBANGAN PENDIDIKAN (Suatu Analisis Implementatif) - Razali M Thaib; Irman Siswanto (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2015)
The curriculum is one of the important components that are crucial in the education system of units, and is a tool to achieve educational goals as well as guidance in the implementation of teaching in all types and levels of education. As a consequence, implementing curriculum in schools should manage well, so that the learning outcomes will be more effective, to realize it, it requires good management. This curriculum management meant that the educational process will take place in schools can be directed and coordinated in a systematic manner to achieve educational goals that have been set. In the management of the curriculum very necessitated a review-a review of theoretical and practical curriculum that can be managed always in line with the development of human life, science, technology and personal development subjects students. to address any problems that arise in the school environment, especially in the field of teaching and learning, it is highly charged policy principal as manager to always involve personnel-school personnel such as teachers, school committees, teachers bimpen and all parties involved in the implementation of the curriculum, to perform periodic review of the curriculum by involving all stakeholders, the curriculum review purposes, as an effective goal to improve learning outcomes are maximized.